The Efficacy and Safety of Sacubitril/Valsartan in Heart Failure Patients: A Review - Rui Zhang MD, PhD; Xiaotong Sun PhD; Ya Li MD, PhD; Wenzheng He MM; Hongguang Zhu MD, PhD; Baoshan Liu MD, PhD; Aiyuan Zhang MD, PhD (SAGE Publishing, 2022)
Heart failure (HF) is one of the leading causes of morbidity and mortality worldwide. Sacubitril/valsartan, an angiotensin receptor-neprilysin inhibitor, has been approved for the treatment of HF. At present, there have been few systematic and detailed reviews discussing the efficacy and safety of sacubitril/valsartan in HF. In this review, we first introduced the pharmacological mechanisms of sacubitril/valsartan, including the reduction in the degradation of natriuretic peptides in the natriuretic peptide system and inhibition of the renin-angiotensin system. Then, we summarized the efficacy of sacubitril/valsartan in HF patients with reduced ejection fraction (HFrEF) or preserved ejection fraction (HFpEF) including the reduction in risks of mortality and hospitalization, reversal of cardiac remodeling, regulation of biomarkers of HF, improvement of the quality of life, antiarrhythmia, improving renal dysfunction and regulation of metabolism. Finally, we discussed the safety and tolerability of sacubitril/valsartan in the treatment of HFrEF or HFpEF. Compared with ACEIs/ARBs or placebo, sacubitril/valsartan showed good safety and tolerability, although the risk of hypotension might be high. In conclusion, the overwhelming majority of studies show that sacubitril/valsartan is effective and safe in the treatment of HFrEF patients but that it has little benefit in HFpEF patients. Sacubitril/valsartan will probably be a promising anti-HF drug in the near future.